(3efJNH ef cJGH eYQaI GdCdbGH d(B: (3CHj HcQ CMeO Hf YHO GdQMef Hf CMeO GdTjQGRjs - (3GdebOSj, CHh GdaVd, GHf GdbjSQGfj, , eMeO Hf WGgQ Hf Ydj, J (B507(3g`s
(3BNQgG (B:s
(3YdjgG aj GdBNQ Cfg fbdgG ef NW GdMGaX CHh GdbGSe Ydj Hf HOd Hf CHj GdeYeQ GdJHQjRj , Ke fbdg ef NW GdebOSj , GdGeGe GdMGaX Ch GdbGSe Ydj Hf GdMSf Hf gHI Gddg HOeTbs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs